THE ROLE OF RELIGIOSITY IN THE PREFERENCES OF MUSLIM HOUSEWIVES IN CHOOSING HALAL FOOD PRODUCTS (A STUDY ON THE MAJELIS TAKLIM AL-ABZAR GROUP) - Sari, Rosmila; Keri, Ismail (Program Studi Manajemen Keuangan Syariah, 2025)
This thesis analyzes the role of religiosity in the preferences of Muslim housewives in choosing halal food products (a study of the Al-Abzar Majelis Taklim Group). The purpose of this study was to determine the role of religiosity in the preferences of Muslim housewives in choosing halal food products (a study of the Al-Abzar Majelis Taklim Group). The type of research used in this study is field research, and from the data analysis, this study is qualitative. Data collection techniques include interviews, observation, and documentation. The data analysis used is qualitative data analysis with the stages of data reduction, data presentation, and conclusion presentation. The results of the study indicate that religiosity strongly influences the preferences of Muslim housewives at the Al-Abzar Islamic Study Group (Majelis Taklim Al-Abzar) in choosing halal food products. This is reflected in their adherence to halal label checks, willingness to replace questionable products, belief that halalness is a sharia obligation, a sense of guilt when consuming questionable products, and support from family and community members who remind each other and share information to ensure food consumption adheres to halal principles. Religious factors contributing to Muslim housewives at the Al-Abzar Islamic Study Group choosing halal food products include adherence to sharia principles by avoiding haram and doubtful elements, good knowledge and understanding of halal certification through outreach, and a strong personal commitment to choosing halal products even if they are more expensive and always seeking halal information before purchasing.